Exploring the formation of the first galaxies with VISTA and JWST - Donnan, Callum T. (The University of Edinburgh, 2025)
With the successful launch of JWST, there is now the ability to robustly detect galaxies at z ≥ 10 for the first time due to the sensitivity of the NIRCam instrument at λ > 2μm. I first reduce and analyse the initial available James Webb Space Telescope (JWST) ERO and ERS NIRCam imaging (SMACS0723, GLASS, CEERS) in combination with the latest deep ground-based near-infrared imaging in the COSMOS field (provided by UltraVISTA DR5) to produce a new measurement of the evolving galaxy UV luminosity function (LF) over the redshift range z = 8 − 15. This yields a new estimate of the evolution of UV luminosity density (ρUV), and hence cosmic star-formation rate density (ρSFR) out to within < 300 Myr of the Big Bang. My results confirm that the high-redshift LF is best described by a double power-law (rather than a Schechter) function up to z ∼ 10, and that the LF and the resulting derived ρᵤᵥ (and thus ρₛբᵣ), continues to decline gradually and steadily up to z ∼ 15 (as anticipated from previous studies which analysed the pre-existing data in a consistent manner to this study). I then utilise JWST NIRCam medium-band imaging centered on the Hubble Ultra Deep Field (HUDF) to search for extreme redshift (z ≥ 9.5) galaxy candidates. My search reveals 6 robust candidates, 3 of which have recently been spectroscopically confirmed. One of these 3 is the previously controversial z ≃ 12 galaxy candidate UDF-22980, which now has a secure photometric redshift of zphot = 11.6±0.2. I determine the physical properties of the 6 galaxies by fitting the 14-band photometry with Bagpipes finding stellar masses of log(M⋆/M⊙) ≃ 7.5 − 8.7 and star-formation rates of log(SFR/M−1 ⊙ yr−1) ≃ 0.3 − 5.0. Despite the relatively small cosmological volume covered by the HUDF itself and the second NIRCam module imaging, I find that the existence of these galaxies is fully consistent with the latest measurements of both the UV luminosity function and cosmic star-formation rate density at z ≃ 11. I then present a new determination of the evolving galaxy UV LF over the redshift range 8.5 < z < 15.5 using a combination of several major Cycle-1 JWST imaging programmes - PRIMER, JADES and NGDEEP. I select a sample of 2548 galaxies with a significant probability of lying at high redshift (p(z > 8.5) > 0.05) to undertake a statistical calculation of the UV LF. My measurements yield a new estimate of the early evolution of the UV LF and cosmic star-formation rate density (ρₛբᵣ) confirming the gradual decline deduced from early JWST studies, at least out to z ≃ 12. Finally I show that the observed early evolution of the galaxy UV LF (and ρₛբᵣ) can be reproduced in a ΛCDM Universe, with no change in dust properties or star-formation efficiency required out to z ≃ 12. Instead, a progressive trend towards younger stellar population ages can reproduce the observations, and the typical ages required at z ≃ 8, 9, 10, and 11 all converge on ≃ 380 − 330 Myr after the Big Bang, indicative of a rapid emergence of early galaxies at z ≃ 12 − 13. Since the launch of JWST there have been a number of surprising results concerning galaxy evolution at z > 6 which are in apparent tension with a number of theoretical models. Here I further develop a simple theoretical model to reproduce the observed evolution of the galaxy stellar mass function (GSMF) and the UV luminosity function (UVLF) at z ≥ 6. A constant star-formation efficiency model is able to both match the latest JWST measurements of the GSMF at z = 6−8 and the UV LF at z = 6−13 in contrast to some suggestions in the literature. I find no evidence for the removal of feedback in high-mass halos (> 10¹¹.⁷M⊙) from the observed GSMF at z ≥ 6 and number density of sub-millimetre galaxies. Instead the bright-end of the UV LF at z ≥ 6 is fully reproducible with dust attenuation given a consistent relationship between UV attenuation and stellar mass with redshift. Finally, the combination of my models of the UV LF with the latest constraints on the escape fraction of Lyman continuum radiation and the production efficiency of ionising photons in galaxies, is fully able to match observational measurements of the timeline of reionization and completion redshift of z ≃ 5.5.
Keywords: JWST; UV Luminosity Function; Redshift; Star-Formation Rate Density; Galaxy Evolution